(untitled) (Horizon Multidisciplinary Scientific Journal, 2026)
Purpose: This study aims to examine the long-term relationship between annual inflation rates and unemployment rates in the Turkish economy over the 64-year period from 1960 to 2023 within the theoretical framework of the Phillips Curve. Method: A quantitative research method was adopted, utilizing annual data obtained from the Turkish Statistical Institute (TÜİK) and the World Bank. The normality assumption of the dataset was tested using the Shapiro-Wilk test, while the existence of a linear relationship was examined through Pearson correlation analysis. In the simple linear regression model estimated by the Ordinary Least Squares (OLS) method, t-statistics and p-values were calculated, and the Gauss-Markov assumptions of the model (linearity, zero conditional mean, homoscedasticity, and absence of autocorrelation) were systematically tested. Additionally, separate analyses were conducted for three sub-periods: 1960-1979, 1980-2001, and 2002-2023. Findings: For the entire period, the Pearson correlation coefficient indicated a statistically significant, moderately positive relationship between inflation and unemployment. Although the OLS regression model produced a significant slope coefficient, its explanatory power remained low. Sub-period analyses revealed that the direction and strength of the relationship varied considerably across different economic regimes. Conclusion: The findings suggest that the traditional Phillips Curve relationship does not hold in Turkey over the long-term 64-year period. Instead, a positive correlation pattern appears to dominate, driven by stagflation dynamics, chronic inflation inertia, and external shocks. These results highlight the need for developing macroeconomic models tailored to developing economies and